Micronized Vaginal Progesterone to Prevent Miscarriage: A Critical Evaluation of Randomized Evidence. Issue 12 (December 2020) - Coomarasamy, Arri; Devall, Adam J.; Brosens, Jan J.; Quenby, Siobhan; Stephenson, Mary D.; Sierra, Sony; Christiansen, Ole B.; Small, Rachel; Brewin, Jane; Roberts, Tracy E.; Dhillon-Smith, Rima; Harb, Hoda; et al.
Abstract : (Abstracted from Am J Obstet Gynecol 2020;223(2):167–176) Historically, a lack of methodologically strong and generalizable studies has limited policy makers from recommending the use of progesterone supplementation to improve outcomes in women at high risk of miscarriage. The PROMISE and PRISM trials were carried out to rectify this and generate robust evidence on the role of progesterone supplementation to prevent miscarriage.